Excision of viral DNA from host cell DNA after induction of simian virus 40-transformed hamster cells. - Rakusanova, T (1976)
Simian virus 40-transformed hamster cells were induced to produce infectious virus by treatment with mitomycin C or gamma-irradiation. A portion of the simian virus-40 DNA, which is integrated into the host cell genome in uninduced cells, was recovered in a pool of relatively low-molecular-weight DNA early after induction treatment in the absence of DNA replication. The data indicte that excision of the viral genome occurs subsequent to the induction stimulus.